Population regulation by enemies of the grass Brachypodium sylvaticum: demography in native and invaded ranges. - Roy, B; Coulson, T; Blaser, W; Policha, T; Stewart, J; Blaisdell, G; Güsewell, S (2011)
The enemy-release hypothesis (ERH) states that species become more successful in their introduced range than in their native range because they leave behind natural enemies in their native range and are thus "released" from enemy pressures in their introduced range. The ERH is popularly cited to explain the invasive properties of many species and is the underpinning of biological control. We tested the prediction that plant populations are more strongly regulated by natural enemies (herbivores and pathogens) in their native range than in their introduced range with enemy-removal experiments using pesticides. These experiments were replicated at multiple sites in both the native and invaded ranges of the grass Brachypodium sylvaticum. In support of the ERH, enemies consistently regulated populations in the native range. There were more tillers and more seeds produced in treated vs. untreated plots in the native range, and few seedlings survived in the native range. Contrary to the ERH, total measured leaf damage was similar in both ranges, though the enemies that caused it differed. There was more damage by generalist mollusks and pathogens in the native range, and more damage by generalist insect herbivores in the invaded range. Demographic analysis showed that population growth rates were lower in the native range than in the invaded range, and that sexually produced seedlings constituted a smaller fraction of the total in the native range. Our removal experiment showed that enemies regulate plant populations in their native range and suggest that generalist enemies, not just specialists, are important for population regulation.